Analysis of Work Engagement, Competence, Motivation Mediated by Resilience on Employee Performance - Ninin Nurhidayati; Joned Ceilendra Saksana; Neila Aisha; Bekti Setiadi; Dewi Ulfah Arini (Indonesian Journal of Business Analytics, 2023)
This study aims to review several articles related to employee performance which has become a phenomenon in the industry, many findings in the industry employee performance is influenced by various variables such as work engagement, competence, motivation and are mediated by resilience, this article uses a literature summary study and there are findings of several variables that are indeed related to employee performance, in this study no sample was used because there was no distribution of questionnaires to respondents.